The examination of the sarcastic posts on social media to the Algerian reality issues -An analytical study of a sample of sarcastic posts on Facebook- - .khalfa, Badra; farzouli, Mokhtar (Journal of Social Sciences and Humanities, 2023)
The study aims at exploring how the sarcastic posts on social media examine the Algerian reality issues which is considered as a recent way to express all the different subjects by the audience in order to highlight the most important covered issues and subjects and also the techniques of presenting the forms of the sarcasm used in dealing with such issues In This analytical study, data were collected through adopting the content analysis tool in which a sample of some sarcastic posts on social media were analyzed by determining the main and subsidiary units and the selected unit of analysis and monitoring the amount of interaction by determining the percentage of both views and likes of each post to get accurate results. The importance of these sarcastic pages relies on the way they criticize all the issues that the Algerian citizen suffers from and this enables to reach results that can make a change in the lived reality in the Algerian society and then to find the appropriate solutions.